Um estudo de utilização de equipamentos de realidade virtual imersiva associados a um sistema de apoio no ensino de poliedros convexos - Bergamaschi, Marcelo Pereira (2005)
The objective of this study is to demonstrate the potentiality of Immersive Virtual Reality (IVR) techniques in computer based teaching/learning process, through the development of virtual educational environments. This research aimed at providing a human-machine form of interaction that would be more familiar and motivating for the user in the context where it took place. This work has as its main objectives: 1) to identify specific devices which better support the development of an educational and immersive virtual environment and 2) to investigate IVR techniques that allow a more natural and intuitive interaction between the user and his study objetc. To evaluate the proposed techniques, a prototype system was developed as a case study, which permitted the user to visualize and interact with the polyhedron surfaces inside a virtual environment making cuts in these surfaces through plans. To reach the interaction proposed in this system, this research identified the need to integrate VRML language and JavaScript in order to explore the positive aspects of both languages and reach the proposed level of interaction. After making the system available to potential users, they were able to do some experiments and confirmed that the techniques proposed are satisfactory and helpful in the learning process and in the visualization of surfaces from 3D cuts, thanks to the IVR proposed techniques.